2020
DOI: 10.1186/s41182-020-00251-6
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant and extended-spectrum beta-lactamase-producing uropathogens in children in Bhaktapur, Nepal

Abstract: Background: The emergence of multidrug-resistant (MDR) and extended-spectrum beta-lactamase (ESBL)producing uropathogens has complicated the treatment of urinary tract infections (UTI). Paediatric UTI is a common illness, which if not treated properly, may lead to acute and long-term complications, such as renal abscess, septicaemia, and renal scarring. This study aimed to determine the prevalence of MDR and ESBL-producing uropathogens among children. Methods: During the study period (April 2017-April 2018), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
4
6
0
Order By: Relevance
“…Similar to other pediatric studies on the same subject (2,20,22), E. coli was the most frequently encountered etiological agent in our research as well.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to other pediatric studies on the same subject (2,20,22), E. coli was the most frequently encountered etiological agent in our research as well.…”
Section: Discussionsupporting
confidence: 90%
“…coli and Klebsiella represented common uropathogens in children admitted to both nephrology departments involved. In this study, the frequency of infection with E. coli and Klebsiella were similar with studies from Nepal and Turkey (20,21).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Higher rates of ESBLs have been reported from Southeast Asia, including Nepal [14]. Various studies have reported the circulation of ESBL-producing bacterial strains in Nepal [3,6,[15][16][17][18]. Laboratory facilities for culture and antimicrobial susceptibility testing in different peripheral/district hospitals are still not available in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to identify ESBL-producing organisms contributes to their uncontrolled spread [12]. Identification of the resistant phenotype is crucial in preventing the AMR, more so in developing countries, where there is excessive use of antibiotics and a lack of adequate antimicrobial resistance surveillance [11,17]. The main objective of this study was to explore the prevalence of ESBL-producing Gram-negative bacteria, their antibiogram, and molecular detection of plasmid-mediated ESBL genes bla TEM and bla CTX-M in E. coli among patients suspected of heart infections at Gangalal Heart Hospital, Kathmandu, Nepal.…”
Section: Introductionmentioning
confidence: 99%